Description of Physiological Changes and Feelings of Anxiety in 1st Trimester Pregnant Women at RSIA Sitti Khadijah 1 Muhammadiyah Makassar Branch - Ismail, Citra Resy; Arfah, Arni Isnaini; Khalid, Nur Fadhillah; Hamsah, M.; Amaliyah B, Ilma Khaerina (Jurnal Biologi Tropis, 2024)
During pregnancy, a pregnant woman's ability to adapt to the changes that occur physically and mentally is necessary. There is no need to worry about this because this change is a normal situation. This study aims to determine the description of physiological changes & feelings of anxiety experienced by pregnant women in the first trimester. The design used in this research is descriptive. The population in this study were pregnant women in the first trimester at RSIA Sitti Khadijah 1 Muhammadiyah Makassar. The sample in this study was 30 respondents and was taken by accidental sampling. Data were collected using a questionnaire on physiological changes in pregnant women in the first trimester and HARS. The results of research on 30 respondents showed that the most physiological changes in pregnant women in the first trimester were feeling tired despite getting enough sleep (86.7%) and craving food or something (83.3%). The change in feelings of anxiety in pregnant women in the first trimester was found to be moderate anxiety (63.3%).